Insecticidal Activity and Insect Repellency of Four Species of Sea Lily (Comatulida: Comatulidae) From Taiwan. Issue 1 (21st January 2016) - Su, Shih-Wei; Lee, Tse-Min; Mok, Hin-Kiu; Chio, Eddie Hang
Abstract: The methanol and ethyl acetate (EA) extracts of four species of sea lily ( Himerometra magnipinna, Comaster multifidus, Comanthina sp., and Comatella maculata ) were evaluated for their insecticidal activity against Yellow-fever mosquito larvae ( Aedes aegypti ) and their repellency against adult Asian Tiger mosquitoes ( Aedes albopictus ). The 24-hr minimum inhibition concentration (MIC) data revealed that the extracts from H. magnipinna and the C. maculata were the most active, killing mosquito larvae at 12.5 ppm. The toxicity of the extracts from these four sea lilies in descending order was H. magnipinna (12.5 ppm), C. maculata (12.5 ppm), C. multifidus (100 ppm), and Comanthina sp . (200 ppm). Furthermore, no significant difference in toxicity was found using either EA or methanol as the extraction solvent. The MIC at 12.5 ppm is promising as an insecticide lead. The repellency study results show that EA is a better solvent for one species ( H. magnipinna ), but the methanol is a better solvent overall. The repellency of these sea lily extracts in descending order was Comanthina sp . MeOH (ED50 at 0.32%), followed by H. magnipinna EA (ED50 at 0.38%), C. multifidus MeOH (ED50 at 0.57%), C. maculata MeOH (ED50 at 0.76%), C. multifidus EA (ED50 at 1.25%), and H. magnipinna MeOH (ED50 at 1.67%). A compound with ED50 <0.5% is considered to be a promising repellant. Among the studied sea lilies, both Comanthina sp. and H. magnipinna have potential to be further developed as mosquito control agents due to their favorable toxicity and repellency.